Selected Aspects of Civil Law in the Context of Digitalization - Marian HORVATH (Communications of International Proceedings, 2021)
With the emerging new technologies, a whole range of changes have been introduced in almost every sphere of social life and those should be reflected in the current legislation in force as well. There are two new aspects in the field of law to be considered in the digital environment related to the impact of digitalization on the norms/rules of civil law in the context of scientific and technological development – taking advantage of the benefits brought by the virtual environment and making processes easier, and protection of the users’ rights, including intellectual property rights. In the proposed paper, the author deals with the issues of civil law – a general branch of private law – in the context of the ongoing digitalization and the changes related to it are discussed with an emphasis placed on the issues of legal acts, contracts and the intellectual property right. The choice of the selected areas results from the fact that it is mainly in these areas of civil law that the most remarkable impact of digitalization on normative rules may be identified.
Keywords: Digitalization; civil law; legal act; contract; intellectual property law.